Fraser Syndrome-Oral Manifestations and a Dental Care Protocol - Talita Lopes de Oliveira; Giselle Rodrigues de Sant'Anna (Hindawi Limited, 2014)
Fraser syndrome is a rare genetic malformation with an autosomal recessive pattern of inheritance and an incidence of consanguinity ranging from 15% to 25%. A 5-year-old male patient who is a carrier of Fraser syndrome initiated treatment in the pediatric dentistry sector. The patient was fed parenterally since birth, experienced recurring bouts of chronic lung disease, and was referred to the pediatric dentistry sector by the medical team. Radiographic examination revealed the presence of all permanent teeth. Supragingival dental calculus, halitosis, and gingival inflammation were also observed. Dental calculus was removed by manual scraping, and chemotherapeutic agents were used, chlorhexidine 0,12%, chlorhexidine gel 2%, and PVP-I, to control the bacterial flora. The patient is still being monitored after an 8-year follow-up period, the complications associated with periodontal disease decreased, and since the initiation of treatment, the patient has not needed to be hospitalized because of chronic lung disease. This study reports the case of a patient diagnosed with Fraser syndrome and describes the clinical manifestations (general and oral).